A CASE STUDY FROM GOLDEN GATE UNIVERSITY: USING COURSE OBJECTIVES TO FACILITATE BLENDED LEARNING IN SHORTENED COURSES - Fulkerth, Robert (Online Learning, 2009)
This paper discusses utilizing course objectives to drive the change of existing 10–15 week undergraduate courses into 8-week courses that feature blended learning tools. To begin the redesign process, instructors and a faculty mentor revisit course objectives for currency, and with an eye toward blended course restructuring. The restructuring is overseen to ensure that standards are met. The resulting course redesign has overarching objectives and weekly objectives tied directly to weekly activities, many of which are blended. In addition to blended tools, the courses are considered blended as to modality in that while there is a weekly face-to-face meeting, there is also a fixed expectation for out of class work, where blended tools find good use. An approach to using blended tools as bridge activities between “last week” and “next week” is also presented. The redesigned classes are proving satisfactory to students and teachers; no differences in student course evaluations with respect to course quality are noted. Some students indicate there is “more work”, which is perhaps a function of the need to better manage student and faculty time management expectations. The redesign has been so successful that it we intend it to become a fundamental institutional faculty development tool.